Atrial-radiofrequency catheter ablation mediated targeting of mesenchymal stromal cells - Schweizer, Patrick Alexander; Krause, Ulf; Becker, Rüdiger; Seckinger, Anja; Bauer, Alexander; Hardt, Cornelia; Eckstein, Volker; Ho, Anthony Dick; Koenen, Michael; Katus, Hugo; Zehelein, Jörg (Stem cells, 2007)
Sinus node dysfunction and high-degree heart block are the major causes for electronic pacemaker implantation. Recently, genetically modified mesenchymal stromal cells (MSCs, also known as “mesenchymal stem cells”) were demonstrated to generate pacemaker function in vivo. However, experimental approaches typically use open thoracotomy for direct cell injection into the myocardium. Future clinical implementation, however, essentially requires development of more gentle methods to precisely and efficiently apply specified stem cells at specific cardiac locations. In a “proof of concept” study, we performed selective power-controlled radiofrequency catheter ablation (RFCA) with eight ablation pulses (30 W, 60 seconds each) to induce heat-mediated lesions at the auricles of the cardiac right atrium of four healthy foxhounds. The next day, allogeneic MSCs (4.3 × 105 cells per kilogram of body weight) labeled with superparamagnetic iron oxide particles (SPIOs) were infused intravenously. Hearts were explanted 8 days later. High numbers of SPIO-labeled cells were identified in areas surrounding the RFCA-induced lesions by Prussian blue staining. Antibody staining revealed SPIO-labeled cells being positive for the typical MSC surface antigen CD44. In contrast, low levels of calprotectin, an antigen found on monocytes and macrophages, indicated negligible infiltration of monocytes in MSC-positive areas. Thus, RFCA allows targeting of MSCs to the cardiac right atrium, adjacent to the sinoatrial node, providing an opportunity to rescue or generate pacemaker function without open thoracotomy and direct injection of MSCs. This method presents a new strategy for cardiac stem cell application leading to an efficient guidance of MSCs into the myocardium. Disclosure of potential conflicts of interest is found at the end of this article.
Frontdoor: First published: 02 January 2009
Gesehen am 26.10.2021